Worker Flows and Labour Market Adjustment during the Great Recession: Evidence from a Large Shock - Hartmut Lehmann; Tiziano Razzolini; Anzelika Zaiceva (Institute for the Study of Labor (IZA), 2015)
This paper analyzes how the labor market adjusts to the Great Recession. To this aim, we use the data for Latvia, a country that has experienced one of the most severe recessions in Europe and a subsequent remarkable recovery. Employing longitudinal EU SILC data and a panel data set constructed by us from various waves of the Latvian Labour Force Survey (LLFS), we estimate worker transitions between labor market states. Labor market adjustment takes place predominantly at the extensive margin since it is driven by flows from permanent wage employment to unemployment. We also show that older, non-Latvian and above all less skilled workers are especially hard hit by the economic crisis. Estimated transitions between four mutually exclusive occupational groups demonstrate that downward mobility is very limited even during the Great Recession. Finally, wage regressions suggest that job mobility is not associated with increased labour productivity during and immediately after the crisis.
Keywords: J6; J21; P20; P23; 330; labour market transitions; job and occupational mobility; Great Recession; Latvia